Social change in Aegean prehistory - Wiersma, Corien; Wiersma, Corien; Wiersma, Corien; Voutsaki, Sofia; Voutsaki, Sofia; Voutsaki, Sofia (Oxbow Books, 2016)
"This volume brings together papers that discuss social change. The main focus is on the Early Helladic III to Late Helladic I period in southern Greece, but also touches upon the surrounding islands. This specific time frame enables us to consider how mainland societies recovered from a 'crisis' and how they eventually developed into the differentiated, culturally receptive and competitive social formations of the early Mycenaean period. Material changes are highlighted in the various papers, ranging from pottery and burials to domestic architecture and settlement structures, followed by discussions of how these changes relate to social change. A variety of factors is thereby considered including demographic changes, reciprocal relations and sumptuary behaviour, household organization and kin structure, age and gender divisions, internal tensions, connectivity and mobility. As such, this volume is of interest to both Aegean prehistorians as to scholars interested in social and material change. The volume consists of eight papers, preceded by an introduction and concluded by a response. The introduction gives an overview of the development of the debate on the explanation of social change in Aegean prehistory. The response places the volume in a broader context of the EH III-LH I period and the broader discussion on social change"--From publisher's website